Bifunctional Tm3+,Yb3+:GdVO4@SiO2 Core-Shell Nanoparticles in HeLa Cells: Upconversion Luminescence Nanothermometry in the First Biological Window and Biolabelling in the Visible - Oleksandr Savchuk; Joan Josep Carvajal Marti; Concepción Cascales; Patricia Haro-Gonzalez; Francisco Sanz-Rodríguez; Magdalena Aguilo; Francesc Diaz (Nanomaterials, 2020)
The bifunctional possibilities of Tm,Yb:GdVO4@SiO2 core-shell nanoparticles for temperature sensing by using the near-infrared (NIR)-excited upconversion emissions in the first biological window, and biolabeling through the visible emissions they generate, were investigated. The two emission lines located at 700 and 800 nm, that arise from the thermally coupled 3F2,3 and 3H4 energy levels of Tm3+, were used to develop a luminescent thermometer, operating through the Fluorescence Intensity Ratio (FIR) technique, with a very high thermal relative sensitivity. Moreover, since the inert shell surrounding the luminescent active core allows for dispersal of the nanoparticles in water and biological compatible fluids, we investigated the penetration depth that can be realized in biological tissues with their emissions in the NIR range, achieving a value of 0.8 mm when excited at powers of 50 mW. After their internalization in HeLa cells, a low toxicity was observed and the potentiality for biolabelling in the visible range was demonstrated, which facilitated the identification of the location of the nanoparticles inside the cells, and the temperature determination.